Enhanced superconducting properties of a YGBCO/Gd-CeO2/YGBCO tri-layer film deposited by pulsed laser deposition. Issue 4 (March 2020) - Liu, Shunfan; Wang, Wei; Liu, Linfei; Zheng, Tong; Li, Yijie
Abstract: To evaluate the inhibition of the REBa2 Cu3 O7-δ (REBCO, where RE is rare earth) film thickness effect, a series of Y0.5 Gd0.5 Ba2 Cu3 O7-δ (YGBCO)/interlayer/YGBCO tri-layer films with Gd-Cerium oxide (CeO2 ) film were prepared under different experimental conditions in this study. The results illustrate that the electric current from the top YGBCO layer could transmit to the bottom YGBCO layer by adding Gd into the CeO2 interlayer with the approximate thicknesses limits of 10 nm. For further increase the electric current carrying capacity, a series of YGBCO/Gd-CeO2 /YGBCO tri-layers were fabricated under different oxygen partial pressures and laser energies. The better crystallinity, and texture, and the smoother surface levels completely eliminated the thickness effect. However, the samples' superconductivity declined sharply at low laser energies. Because the Gd particles deposited on the substrate were fully oxidized, this led to particle disappearance in the interlayer film. Additionally, YGBCO samples with a Gd-CeO2 interlayer were more likely to be damaged than a pure YGBCO sample in the measurement process, which could be solved by increasing the Gd content in the CeO2 +Gd target. Hence, by depositing a Gd-CeO2 interlayer, YGBCO tri-layer films with high superconductivity and low damageability were obtained.